2020
DOI: 10.34117/bjdv6n8-652
|View full text |Cite
|
Sign up to set email alerts
|

A Cultura Da Palma, Origem, Introdução, Expansão, Utilidades E Perspectivas Futuras: Revisão De Literatura

Abstract: RESUMOA presente revisão tem como objetivo explicitar conceitos e informações sobre a cultura da palma, sua origem, introdução, expansão, cultivo, pragas, doenças e uso na alimentação humana e animal. A palma é uma cactácea exótica de origem Mexicana que foi trazida para o Brasil pelos colonizadores, no decorrer dos anos descobriu seu uso na alimentação animal, além da humana, pode ser considerada na atualidade como um dos cactos mais cultivados em regiões de climas áridos e semiáridos devido a sua elevada ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
0
6
0
2
Order By: Relevance
“…The only pest that affected the evaluated cactus pear genotypes was Cochineal in scales (22.69%). To avoid the occurrence of diseases in a cactus culture, healthy cladodes should be selected and free from contamination, through proper planting, correcting the soil fertility and with cultural treatments, it is unlikely that the cactus culture will be affected by diseases, because in this case culture most diseases that occur are caused by fungi (VASCONCELOS et al, 2009;NASCIMENTO et al, 2020;MACÊDO et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The only pest that affected the evaluated cactus pear genotypes was Cochineal in scales (22.69%). To avoid the occurrence of diseases in a cactus culture, healthy cladodes should be selected and free from contamination, through proper planting, correcting the soil fertility and with cultural treatments, it is unlikely that the cactus culture will be affected by diseases, because in this case culture most diseases that occur are caused by fungi (VASCONCELOS et al, 2009;NASCIMENTO et al, 2020;MACÊDO et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The cactus genotypes Nopalea Uruapan (V20) and California (V14) had the lowest mortality rate (20 and 35%), respectively. According to the mortality rate assessment, it was found that under the same conditions as the nine cactus genotypes evaluated, the mortality rate above 50% indicates that these genotypes probably did not show adaptability to the conditions to which they were exposed, because in addition to the high rate of mortality will possibly present low agronomic performance, due to the production yield of dry and green matter decreasing as the plant population per hectare also decreases (MACÊDO et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Na região Nordeste se concentra mais de 94% do total, de mais de 8,2 milhões de cabeças de caprinos (IBGE, 2017). O sistema de produção predominante, nessa região é praticamente o extensivo altamente dependente da vegetação nativa da Caatinga (Macêdo et al, 2020), e utilizando, em sua grande maioria, animais sem padrão de raça definida (SRD). Com isso, tem-se despertado discussões a cerca dos níveis produtivos desses animais sob condição de pastejo e a utilização de diferentes alternativas de manejo nutricional e suplementação (Harun et al, 2017), visando melhorar os índices de produtividade do sistema produtivo.…”
Section: Introductionunclassified